2-8m=14-3+8m

Simple and best practice solution for 2-8m=14-3+8m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-8m=14-3+8m equation:


Simplifying
2 + -8m = 14 + -3 + 8m

Combine like terms: 14 + -3 = 11
2 + -8m = 11 + 8m

Solving
2 + -8m = 11 + 8m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-8m' to each side of the equation.
2 + -8m + -8m = 11 + 8m + -8m

Combine like terms: -8m + -8m = -16m
2 + -16m = 11 + 8m + -8m

Combine like terms: 8m + -8m = 0
2 + -16m = 11 + 0
2 + -16m = 11

Add '-2' to each side of the equation.
2 + -2 + -16m = 11 + -2

Combine like terms: 2 + -2 = 0
0 + -16m = 11 + -2
-16m = 11 + -2

Combine like terms: 11 + -2 = 9
-16m = 9

Divide each side by '-16'.
m = -0.5625

Simplifying
m = -0.5625

See similar equations:

| t^2-24=2t | | k^2-20k-35=0 | | g(x)=x+7(2x)2x+14 | | 11/18x^2-7x-56=0 | | 0.6111x^2-7x-56=0 | | 4(x+2)=3(2x-(6-x)) | | 35x+12=4x+3 | | f(x)=2x(x+7)2x^2+14 | | 30=(5/9)(F-32) | | 30(9/5) | | x=(3)(3)(3) | | (6x+7)(2x+1)= | | 5n^2+13n-28=0 | | -4.9t^2+10t+2=0 | | 8-9p=1 | | 15a^2-22a-5=0 | | (3a+2)(a-2)= | | (-3)-(-10)= | | ((-7)-3)((-3)-(10))= | | x/5-x/10=3 | | 2x^4-6x^3+x^2+3=0 | | 13(2-x)=7(x+8) | | 5x+3x^2=25 | | c/a-p/a=1 | | f(x)=tan*3*x | | 6(x-3)-5=21x-4-10x | | 2x+x=59 | | 35+x+2x=42+9x | | 50-8x-3=15 | | 50-8x-3=16 | | 50-8x-3=18 | | 50-8x-4=18 |

Equations solver categories